With ‘Our Father’ through the centuries of Russian poetry - Prus, Kazimierz (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
Christians’ main prayer, ‘Our Father,’ has often been paraphrased in Russian poetry because of its theological and existential intentions. As early as in the Classicism such writers as Sumarokov or Golenishchev-Kutuzov reproduce its content quite faithfully, preserving the simplicity and directness of the text. In the Romanticism, Oratio Dominica is in its paraphrases enriched by emotional elements (Pushkin), presents elevated religious feelings (Fet), contains an added doxology (Oznobishin), significantly increases in length (Küchelbecker) and begins to deviate from the original imagery (Polonsky). Modernist writers tend to interpret the poetical prayer, they underscore particular requests in it (Fofanov, Chumina) or considerably change its poetical structure and length of the text (Korinfsky). The youngest authors represent an unconstrained attitude to the content of the prayer and transform it into an individual entreaty.